1997
DOI: 10.1021/jp9627234
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic Autoxidation of Tetralin Catalyzed by Surface-Active Transition Metal Complexes

Abstract: Biphasic autoxidation of tetralin has been carried out using surface-active tetramethylethylenediamine complexes of manganese, chromium, and nickel as catalysts, tetralin as the substrate and organic phase, and dodecyl sodium sulfate as emulsifier. Advantages of the biphasic reaction over the homogeneous and heterogeneous counterparts include avoidance of the use of a troublesome solvent, ease of catalyst recovery and substrate recycle, and attainment of high reactivity, selectivity, and reproducibility under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…However, we have not detected the presence of this hydroperoxide in the current system, perhaps due to its fast decomposition to the final products [1]. The metal-catalyzed decomposition of tetralyl hydroperoxide, which has been extensively reviewed in the literature [28][29][30][31], could also be responsible for its fast loss. Another common by-product in such reactions is naphthalene [32].…”
Section: Bond Lengthsmentioning
confidence: 70%
“…However, we have not detected the presence of this hydroperoxide in the current system, perhaps due to its fast decomposition to the final products [1]. The metal-catalyzed decomposition of tetralyl hydroperoxide, which has been extensively reviewed in the literature [28][29][30][31], could also be responsible for its fast loss. Another common by-product in such reactions is naphthalene [32].…”
Section: Bond Lengthsmentioning
confidence: 70%
“…The zeroth-order rate dependence on P CO above 450 mmHg, which may be explained in terms of the palladium complex existing predominantly in a carbonylated form (see section III-J), brings the biphasic carbonylation of α-methylbenzyl bromide partially in line which other biphasic catalytic reactions that show zeroth-order dependence on dissolved gas reactants. ,, It appears that the segregation of a surface-active catalyst complex at the O−W interface, coupled with the affinity of the catalyst complex for the dissolved gas reactant, creates a localized high concentration of the dissolved gas reactant around the interface and lessens the dependence on the dissolved gas, except at a low concentration. The fact that the zeroth-order regime in the rate profile in this case is preceded by a prominent first-order regime may be attributed to a lower stability constant of the palladium−phosphine complex in the alcoholic biphasic medium and a lower concentration of the catalyst complex at the O−W interface.…”
Section: Resultsmentioning
confidence: 98%
“…Recent studies from our laboratory have demonstrated the feasibility and advantages of using an organic−water (hereafter, O−W) interfacial technique to synthesize α-tetralone, phenylacetic and phenylenediacetic acids, poly(2,6-dimethyl-1,4-phenylene oxide), and aromatic polyamides. Interfacial synthesis offers some significant advantages over conventional syntheses (homogeneous or heterogeneous), and these include (1) avoidance of the use of a toxic or environmentally troublesome solvent that may otherwise be needed, (2) use of a pseudo-homogeneous catalyst that is characterized by high reactivity, selectivity, and reproducibility under mild reaction conditions, (3) ease of catalyst recovery unaffected by the solubilities of the reactants and products in either the aqueous or organic phase, (4) possibility of a simultaneous reaction−separation scheme whereby a desired product can be removed to prevent further reaction, (5) ease of operation and control, (6) avoidance of an adverse gelling effect on a polymerization reaction, (7) a higher solubility for a gaseous reactant than in an aqueous system, (8) a higher reaction rate due to the concentrating and intimate-contacting effects of the interface on the reactant(s) and catalyst, and (9) possibility of regio- and stereoselectivity control on account of the directional influence of the interface on molecular orientations.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, 1-tetralin was chosen as a substrate, because the metal-catalyzed aerobic oxidation [8] of this molecule is an intermediate step in the commercial production of α-naphthol [9,10], and 1-tetralone acts as the starting material for the manufacture of the commercial insecticide Carbaryl [11].…”
Section: Introductionmentioning
confidence: 99%